Contrastive analysis of politeness strategies in refusal speech acts: A study of Sundanese and Batak language - Rossy Halimatun Rosyidah (English Learning Innovation)
This research examines politeness strategies in refusal speech acts used by Sundanese and Batak speakers. The purpose of this research is to test the truth of the stereotype which states that Batak people tend to be loud or rude, while Sundanese people are considered smooth and polite in communicating. This research used a qualitative methodology and a contrastive analysis approach. A total of ten informants participated in this research, consisting of five native Toba Batak speakers and five native Sundanese speakers who were around fifty years old. Data were collected through the Discourse Completion Task (DCT). Data analysis uses Miles et al., (2014) interactive model, which involves three stages: data condensation, data presentation, and verification. Data validity uses triangulation. The findings show that Batak and Sundanese speakers both use negative politeness strategies, while Sundanese speakers also use positive politeness strategies. Negative politeness is used to maintain relationships while respecting the rights of the interlocutor, for example by expressing regret, giving clear reasons, or emphasizing personal inability to fulfil requests and positive politeness strategies are used to maintain harmony and show attention to the feelings of the interlocutor. They avoid using the bald-on-record strategy (direct rejection without further ado). These findings show that the stereotypes that exist in society are not true, both Batak and Sundanese speakers prioritize respect and harmony in communication